A secure online quiz system - Lin, Dekun (2014)
Online assessment is gaining huge popularity as an education tool, due to its pedagogical effects and cost-effective feature. Prevention of cheating is vital for a reliable online assessment system, and while it is usually resolved by implementing sophisticated plagiarism detection algorithms, most current systems are restricted to perform dynamic creation of questions, which is proved another promising way of addressing the problem. The objective of the Final Year Project is to design and develop a web-based and secure Online Quiz System (OQS) that focuses on four featured functionalities: 1. Effortless setup of parameterized image-embeddable questions that support four different types, including multiple-choice, multiple-response, fill-in-blank, and essay. 2. Automated and intelligent grading of results with customizable marking rules. 3. Simultaneous detection and prevention of cheating by mandatory full screen, key logging and locking, network monitoring, periodic photo capturing, front- end and back-end validation and system logging. 4. Convenient administration and management of users with different access levels. In the integrated with an external program for security support, has been developed and delivered with all requirements fulfilled. The web application, which consists of 34168 lines of code in total, is built on LAMP (Linux, Apache HTTP Server, MySQL and PHP) solution stack in two-tier client/server architecture. The development process has gone through a series of phases consistent with Software Development Life Cycle, which involves mainly requirement analysis, database design of 13 tables, user interface design, implementation of back-end and client-end functions, integration with security program, and black box testing. Results have shown OQS’s capability as a reliable and effective assessment tool.